Overview of Wireless Access in Vehicular Environment (WAVE) protocols and standards - M. Ahmed, Shereen A. (2013)
Institute of Electrical and Electronics Engineers (IEEE) series of standards for Wireless Access in Vehicular Environment (WAVE) is currently considered as the most promising technology for vehicular networks. It aims to support interoperabil - ity and robust safety communications in a vehicular environment. The first trial version of WAVE standard was released in 2006, Most of the published review studies were done on the old trail versions. This study reviews the latest released version of the IEEE WAVE standard, reflects the state of art in WAVE technology, and presents the status of each standard in the IEEE 1609 series of standards. IEEE 1609 series contains four standards that are under development, three are published and one is already withdrawn. Then the study discusses the technical details of IEEE 1609.4 for multi-channel operation and highlights the new features of WAVE Media Access Control ( MAC ) layer. The study also describes the services and protocols that are provided by IEEE 1609.3 as a network service standard. Frame format that is used in standards are also exposed.